Thyme Essential Oil as a Potential Tool Against Common and Re-Emerging Foodborne Pathogens: Biocidal Effect on Bacterial Membrane Permeability - Martina Di Rosario; Leonardo Continisio; Giuseppe Mantova; Francesca Carraturo; Elena Scaglione; Daniela Sateriale; Giuseppina Forgione; Chiara Pagliuca; Caterina Pagliarulo; Roberta Colicchio; Mariateresa Vitiello; Paola Salvatore (Microorganisms)
Over the past decade, foodborne diseases have become a significant public health concern, affecting millions of people globally. Major pathogens like Salmonella spp., Escherichia coli, Listeria monocytogenes, and Staphylococcus aureus contaminate food and cause several infections. This study investigates the potential of thyme essential oil (Thy-EO) as a natural antimicrobial agent against most common and re-emerging foodborne bacteria, including S. enterica, Yersinia enterocolitica, and L. monocytogenes. Preliminary tests provided qualitative evidence of Thy-EO’s efficacy by evaluating its antibacterial activity through direct contact and vapor phase exposure. Then, the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were defined to quantitatively evaluate the bacteriostatic and bactericidal effects of Thy-EO, revealing a strong inhibitory effect against S. enterica, Y. enterocolitica and L. monocytogenes. Additionally, Thy-EO exerted rapid bactericidal kinetics characterized by the disruption of bacterial cell membrane integrity over time. Results highlight Thy-EO’s potential as an alternative antimicrobial agent, demonstrating that treatment with Thy-EO significantly and irreversibly affects the growth of the tested foodborne pathogens.